2022
DOI: 10.1111/all.15449
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells and immunoglobulin E: A new therapeutic link for autoimmunity?

Abstract: Autoimmune diseases have a prevalence of approximately 7 to 9% and are classified as either organ‐specific diseases, including type I diabetes, multiple sclerosis, inflammatory bowel disease and myasthenia gravis, or systemic diseases, including systemic lupus erythematosus, rheumatoid arthritis and Sjögren's syndrome. While many advancements have been made in understanding of the mechanisms of autoimmune disease, including the nature of self‐tolerance and its breakdown, there remain unmet needs in terms of ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 153 publications
0
9
0
Order By: Relevance
“…Likewise, WIN-hmoDCs primed FOXP3 + Tregs and displayed reduced capacity to polarize both Th1 and Th2 responses. The induction and/or expansion of Tregs is essential to keep homeostasis in the context of immune-mediated and inflammatory diseases (31)(32)(33), which might be regulated by exogenous signals including cannabinoids like cannabidiol (CBD), JTE907 or O-1966 (34)(35)(36). We previously showed that fully differentiated conventional hmoDCs and blood DCs subsets stimulated in vitro with toll-like receptor ligands in the presence of promote functional Tregs (13,37,38), which was further corroborated in vivo in LPS-induced sepsis, peanut-allergic sensitization and anaphylaxis models (13,37).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, WIN-hmoDCs primed FOXP3 + Tregs and displayed reduced capacity to polarize both Th1 and Th2 responses. The induction and/or expansion of Tregs is essential to keep homeostasis in the context of immune-mediated and inflammatory diseases (31)(32)(33), which might be regulated by exogenous signals including cannabinoids like cannabidiol (CBD), JTE907 or O-1966 (34)(35)(36). We previously showed that fully differentiated conventional hmoDCs and blood DCs subsets stimulated in vitro with toll-like receptor ligands in the presence of promote functional Tregs (13,37,38), which was further corroborated in vivo in LPS-induced sepsis, peanut-allergic sensitization and anaphylaxis models (13,37).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have revealed an increase in the pathogenic Th17 cells in patients, which contribute to the pathogenesis of SS 11 . Since Treg cells are the main suppressors of the excessive activation of immune responses, the recent advances in the therapeutic strategy of SS are to target Treg homeostasis or its associated signaling pathway 34 . Here we found that PTEN knockdown decreased the Treg/Th17 ratio in SPLCs, and that VIP treatment increased the Treg/Th17 ratio and the expression of PTEN.…”
Section: Discussionmentioning
confidence: 99%
“…Autoreactive IgE, such as anti-dsDNA IgE, was found to be elevated in SLE patients and can also elicit an increase in IFNα production by binding the Fc epsilon RI (FcεRI) of plasmacytoid dendritic cells (pDCs) [ 17 ]. The binding of IgE to pDCs also enhances the follicular T cell expansion and reduces the Treg population, which increased the inflammatory condition in lupus patients [ 18 ]. IFN-α can also activate the IL-1 receptor-associated kinase that further induces apoptosis in Treg cells from SLE patients [ 19 ].…”
Section: Sle Immunobiologymentioning
confidence: 99%